The Global Value Chains of Manufacturing in Mexico (2005-2015) (2020)
Mexico is one of the most integrated economies in GVC, particularly with the United States in the automotive industry. The objective of this article is to analyze the integration of the manufacturing sector in CGV, taking into account the deepening of transformation activities and the relationship with labor markets. In doing so, we use Trade in Value Added (TiVA) and Trade in eMployment (TiM) databases published by the OECD. We found that Mexico’s manufacturing sector is strongly integrated in GCV, especially with the United States, covering a high proportion of added-value exports and jobs created by exports. Nonetheless, the integration exposes Mexican manufacturing sector to two main challenges: US trade policy changes and automation.